EVALUASI PERATURAN DAERAH NOMOR 10 TAHUN 2007 TENTANG KETERTIBAN SOSIAL DI KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Annida Ulfah; Ridho Al-Hamdi (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2020)
ABSTRACT. This paper evaluates the social order policy, namely Local Regulation Number 10 the Year 2007 concerning the social order in Banjar Regency. In addition to that, this study attempts to find out the driving factors influencing the success and failure of the regulation. Methodologically, this study employs a qualitative method with a study case approach. To gather data, it uses documentation and in-depth interviews. To measure the evaluation, this study adopts six indicators: effectiveness, efficiency, adequacy, equality, responsiveness, and accuracy. The finding demonstrates that among six indicators, only one indicator has succeeded, i.e. equality. In the meantime, five other indicators were unsuccessful. It can be concluded that the policy of the social order evaluation was unsuccessful. Several factors were influencing the failure of the regulation: effectiveness, adequacy, and equality. Therefore, the government performance needs a serious effort to address this problem without any exception and execute all society’s behaviour which contradicted with this policy. Key words: Evaluation; Sosial order; shariah regional regulation; Banjar Regency.